Transferrin and folic acid co-modified bufalin-loaded nanoliposomes: preparation, characterization, and application in anti-cancer activity - Chen Q (Dove Medical Press, 2018)
Qiankun Chen,1 Ji Liu2 1Department of Thoracic Surgery, Shanghai Pulmonary Hospital, Tongji University School of Medicine, Shanghai, China; 2Department of Anesthesia, Shanghai Pulmonary Hospital, Tongji University School of Medicine, Shanghai, China Aim: The aim of this study was to prepare transferrin (Tf) and folic acid (FA) co-modified bufalin (BF) liposomes for lung cancer treatment.Method: In this study, (FA+Tf) BF-LPs were prepared using the high-pressure homogenization method.Results: The EE% and DL% of prepared LPs were 82.3% and 10.7%, respectively, and the mean diameter was 120.4 nm from three batches. In vitro release showed that the release of BF from (FA+Tf) BF-LPs was slow with burst effects at an early stage. In vitro cytotoxicity assay showed that (FA+Tf) BF-LPs had a superior antiproliferative effect on A549 cells. An in vivo imaging study indicated that (FA+Tf) BF-LPs had obvious targeting characteristics on subcutaneous tumor, with the potential to actively deliver drugs to tumor tissues. In terms of the in vivo antitumor activity, (FA+Tf) BF-LPs treated mice showed a significantly suppressed tumor growth and no systemic toxicity in the body.Conclusion: Through this study, it was found that the Tf and FA co-modified BF could be a very promising lung target preparation. Keywords: transferrin, folic acid, liposomes, bufalin, in vivo imaging, antitumor activity